The last gunfight : the real story of the shootout at the O.K. Corral and how it changed the American west - Guinn, Jeff (Simon & Schuster, 2011)
A revisionist history of the Old West battle challenges popular depictions of such figures as the Earps and Doc Holliday, tracing the influence of a love triangle, renegade Apaches, and the citizens of Tombstone.